Omega-3 PUFAs and vitamin D co-supplementation as a safe-effective therapeutic approach for core symptoms of autism spectrum disorder: case report and literature review. (2nd October 2020) - Infante, Marco; Sears, Barry; Rizzo, Angela Maria; Mariani Cerati, Daniela; Caprio, Massimiliano; Ricordi, Camillo; Fabbri, Andrea
ABSTRACT: Introduction: Autism spectrum disorder (ASD) is a group of neurodevelopmental disorders characterized by abnormal development of cognitive, social, and communicative skills. Although ASD aetiology and pathophysiology are still unclear, various nutritional factors have been investigated as potential risk factors for ASD development, including omega-3 polyunsaturated fatty acids (PUFAs) and vitamin D deficiency. In fact, both omega-3 PUFAs and vitamin D are important for brain development and function. Case report: Herein, we report the case of a 23-year-old young adult male with autism who was referred to our Unit due to a 12-month history of cyclic episodes of restlessness, agitation, irritability, oppositional and self-injurious behaviours. Laboratory tests documented a markedly altered omega-6/omega-3 balance, along with a vitamin D deficiency, as assessed by serum levels of 25-hydroxyvitamin D. Omega-3 and vitamin D co-supplementation was therefore started, with remarkable improvements in ASD symptoms throughout a 24-month follow-up period. A brief review of the literature for interventional studies evaluating the efficacy of omega-3 or vitamin D supplementation for the treatment of ASD-related symptoms is also provided. Conclusion: To our knowledge, this is the first case reporting remarkable beneficial effects on ASD symptoms deriving from omega-3 and vitamin D combination therapy. This case report suggests omega-3 and vitamin D co-supplementation as a potential safe-effective therapeutic strategy to treat core symptoms of ASD. However, larger studies are needed to evaluate the real efficacy of such therapeutic approach in a broader sample of ASD patients.